CT indices for the diagnosis of hepatic steatosis using non-enhanced CT images: development and validation of diagnostic cut-off values in a large cohort with pathological reference standard. - Byun, Jieun; Lee, Seung Soo; Sung, Yu Sub; Shin, Youngbin; Yun, Jessica; Kim, Ho Sung; Yu, Eun sil; Lee, Sung-Gyu; Lee, Moon-gyu (European Radiology, 2019)
Objectives: To compare the performances of CT indices for diagnosing hepatic steatosis (HS) and to determine and validate the CT index cut-off values.Methods: Three indices were measured on non-enhanced CT images of 4413 living liver donor candidates (2939 men, 1474 women; mean age, 31.4 years): hepatic attenuation (CTL), hepatic attenuation minus splenic attenuation (CTL-S), and hepatic attenuation divided by splenic attenuation (CTL/S). The performances of these CT indices in diagnosing HS, relative to pathologic diagnosis, were compared in the development cohort of 3312 subjects by receiver operating characteristic (ROC) analysis. The cut-off values for diagnosing HS > 33% in the development cohort were determined at 95% specificity and 95% sensitivity using bootstrap ROC analysis, and the diagnostic performance of these cut-off values was validated in the test cohort of 1101 subjects.Results: CTL-S showed the highest performance for diagnosing HS ≥ 5% and HS > 33% (areas under the curve (AUCs) = 0.737 and 0.926, respectively), followed by CTL/S (AUCs = 0.732 and 0.925, respectively) and CTL (AUCs = 0.707 and 0.880, respectively). For CT scans using 120 kVp, the CTL-S cut-off values for highly specific (i.e., - 2.1) and highly sensitive (i.e., 7.6) diagnosis of HS > 33% resulted in a specificity of 96.4% with a sensitivity of 64.0% and a sensitivity of 97.3% with a specificity of 54.9%, respectively, in the test cohort.Conclusion: CT indices using liver and spleen attenuations have higher performance for diagnosing HS than indices using liver attenuation alone. The CTL-S cut-off values in this study may have utility for diagnosing HS in clinical practice and research.Key Points: • CT indices based on both liver attenuation and spleen attenuation (CTL-Sand CTL/S) have higher diagnostic performance than CTLbased on liver attenuation alone in diagnosing HS using various CT techniques. • The CT index cut-off values determined in this study can be utilized for reliable diagnosis or to rule out subjects with moderate to severe HS in clinical practice and research, including the selection of living liver donors and the development of cohorts with HS or healthy controls.